What Has Changed for Clients of the Bioenergetics Approach to Therapy in the Realm of Their Relationship with God? - Allard, James L. (Bioenergetic Analysis, 2022)
This article is an abridgement of a 112-page doctoral phenomenological research paper bearing the same title. The research was based on five case studies and answers the questions of whether and how Bioenergetics therapy influences one’s relationship with God. Using John Conger’s Jung and Reich, Jung’s Modern Man in Search of a Soul, Alexander Lowen’s The Spirituality of the Body and many other of their writings, it systematically compares the participants’ testimonies to the literature concerning grounding, selfhood, relationship, love and faith. It also answers the question of who or what God is in parallel to what Jung, Reich and Lowen have written on the subject and explores the topic of the discovery of God through a connection with the body.